Engineering Expression Cassette of pgdS for Efficient Production of Poly-γ-Glutamic Acids With Specific Molecular Weights in Bacillus licheniformis - Wang, Dong; Wang, Huan; Zhan, Yangyang; Xu, Yong; Deng, Jie; Chen, Jiangang; Cai, Dongbo; Wang, Qin; Sheng, Feng; Chen, Shouwen (Frontiers in Bioengineering and Biotechnology, 2020)
Poly-γ-glutamic acid (γ-PGA) is an emerging biopolymer with various applications and γ-PGAs with different molecular weights exhibit distinctive properties. However, studies on the controllable molecular weights of biopolymers are limited. The purpose of this study is to achieve production of γ-PGAs with a wide range of molecular weights through manipulating the expression of γ-PGA depolymerase (PgdS) in Bacillus licheniformis WX-02. Firstly, the expression and secretion of PgdS were regulated through engineering its expression elements (four promoters and eight signal peptides), which generated γ-PGAs with molecular weights ranging from 6.82×104 to 1.78×106 Da. Subsequently, through combination of promoters with signal peptides, the production of γ-PGAs with a specific molecular weight could be efficiently obtained. Interestingly, the γ-PGA yield increased with the reduced molecular weight in flask cultures (Pearson correlation coefficient of -0.968, P<0.01). Finally, in batch fermentation, the highest yield of γ-PGA with a weight-average molecular weight of 7.80×104 Da reached 39.13 g/L under glutamate-free medium. Collectively, we developed an efficient strategy for one-step production of γ-PGAs with specific molecular weights, which have potential application for industrial production of desirable γ-PGAs.